2022
DOI: 10.20302/nc.2022.31.25
|View full text |Cite
|
Sign up to set email alerts
|

Dragonfly fauna (Insecta: Odonata) of Papuk Nature Park, Croatia

Abstract: Odonata is an amphibious insect order constituting an important link between aquatic and terrestrial habitats. Members of the group are widely used as bioindicators of freshwater habitat health. The Odonata fauna of a total of 44 freshwater habitats in the wider area of Papuk Nature Park was investigated in the spring and summer of 2017 and 2019. Twenty-three lotic and 21 lentic habitats were included in the study. We recorded 39 Odonata species, witha higher species richness (i.e. 35) documented at lentic tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Having in mind that in Montenegro the species has been established since 2008 (De Knijf et al, 2013) the colonization was expected to occur even sooner. The species might have been established in Croatia for some years now, but this was not confirmed sooner due to the lack of targeted odonatological studies in most of the country, with some rare recent examples (Vilenica et al, 2011;Vinko & Vilenica, 2013;Vilenica & Dijkstra, 2014;Vilenica, 2017;Štih et al, 2020;Štih & Koren, 2022).…”
Section: Speciesmentioning
confidence: 99%
“…Having in mind that in Montenegro the species has been established since 2008 (De Knijf et al, 2013) the colonization was expected to occur even sooner. The species might have been established in Croatia for some years now, but this was not confirmed sooner due to the lack of targeted odonatological studies in most of the country, with some rare recent examples (Vilenica et al, 2011;Vinko & Vilenica, 2013;Vilenica & Dijkstra, 2014;Vilenica, 2017;Štih et al, 2020;Štih & Koren, 2022).…”
Section: Speciesmentioning
confidence: 99%
“…49 In addition to the macrolithal, moss was also a preferred habitat for Protonemura, which explains the higher number of individuals found on artificial substates in comparison to the natural habitat. 50 The spring area of the Jankovac stream had a large abundance of Trichoptera, 38,48 as confirmed with the number of individuals found on the natural substrate, but only a small number on artificial substrates. We conclude that their body size and cases make them slow colonisers 51,52 The order Coleoptera are slow colonisers, achieving maximum values during winter, which could explain the relatively low abundance found on the artificial substrates.…”
Section: Discussionmentioning
confidence: 76%
“…14,28 Unlike previous research, a noticeably higher number of Diptera and Ephemeroptera was found in the present study. 38,46,48 Although the abundance of Baetidae and Chironomidae was very high in natural samples, they were much more abundant in artificial substrates, that is, they colonised artificial substrates very well. A good colonisation pattern in the open canopy area was also seen for Simuliidae individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The most numerous and/or the most frequently recorded species were Orthetrum albistylum (Figure 3a) and Sympetrum sanguineum (Figure 3b) from the suborder Anisoptera, and Platycnemis pennipes (Figure 3c) and Calopteryx splendens among the representatives of the suborder Zygoptera. Orthetrum albistylum prefers sunny standing water habitats (ponds, lakes, oxbows) (Dijkstra and Lewington 2006), but it was also recorded in the lentic habitats with little or no aquatic vegetation (Vilenica et al 2011(Vilenica et al , 2020a. Sympetrum sanguineum prefers sunny lentic habitats with well-developed riparian vegetation (Dijkstra and Lewington 2006), and it is possible that most of the recorded individuals originate from the Ferdinandovac oxbow (study site 10) or from some other sunny oxbow with well-developed vegetation located in the vicinity of our study sites.…”
Section: Results and Discussion -Rezultati I Raspravamentioning
confidence: 99%